Comprehensive Construction of the Interface Structure and Pathways for Building a Sound Relationship between Government and Business - Jiang, Yanbin; Zhang, Wei (Transactions on Social Science, Education and Humanities Research, 2023)
The comprehensive and close relationship between government and business is a distinctive social connection where contemporary political power, administrative resources, and commercial activities interweave. This relationship is a requirement outlined in Article 25 of the 2023 "Opinions of the CPC Central Committee and the State Council on Promoting the Development and Growth of the Private Economy." The comprehensive and close relationship between government and business directly influences the national political and business ecology. This relationship manifests a significant interface structure and a boundary constraint system. The boundary consists of a boundary wall, boundary gate, permeability, and the law of boundary exchange. The boundary constraint system possesses specific functions and value pursuits. Power is the boundary, and interests are the shell; seeking profits through power, defending rights through interests. Power and rights form the interface structure of the political ecology of the comprehensive and close relationship between government and business; public and private interests constitute the boundary in the business ecology of this relationship; the integration of politics and business is reflected in permeability and the law of boundary exchange. The balance between power and interests forms the boundary in the political ecology of the comprehensive and close relationship between government and business. The expansion of private interests and the abuse of public power are boundaries; the exercise of power and its supervision are shells; profitability and gains are the boundary in the political ecology of the business ecology. Profitability and profits are boundaries; to be or not to be is the shell; political, legal, and business integration form the foundational construction of the comprehensive and close relationship between government and business, and it is also the path that structures the boundary system of this relationship. Constructing a boundary system for the comprehensive and close relationship between government and business can enhance the governance capabilities and levels of both the entire political and business ecologies. Political thinking, legal thinking, and business thinking constitute the thinking principles of an integrated government-business boundary system. Compliance, legality, and legitimacy form the integrated boundary structure path for the comprehensive and close relationship between government and business. Rules, systems, and culture can eliminate "politicking without principles and rules" and "business without moral and legal bottom lines." An integrated government-business boundary system can optimize the political-business ecology, creating a fair, transparent, and rule-of-law development environment and fostering a favorable atmosphere for the healthy growth of businesses.